The Influence of Profitability, Liquidity and Leverage on Tax Aggressiveness of Pharmaceutical Companies Listed on the Indonesia Stock Exchange - Louis Yosen Primsa Tarigan (Universitas Pelita Harapan, 2023)
Tax is a vital part to the country's economy and the well-being of its citizens as it is a source of state revenue. However, while the government considers it is crucial to collect taxes, companies view taxes as a reduction of companies’ profits. As a result, businesses strive to keep tax payments to a minimum, either in a legal or illegal way. This behavior is called tax aggressiveness.This study aims to examine the influence of profitability, liquidity, and leverage on tax aggressiveness. The sample is 8 pharmaceutical companies listed on the Indonesia Stock Exchange with the research period of four years (2018-2021) selected through purposive sampling method. The data analysis technique used in this research is multiple linear regression analysis which is processed through SPSS 26.The results show that liquidity and leverage have a significant influence on tax aggressiveness. Meanwhile, profitability has an insignificant influence on tax aggressiveness. Simultaneously, profitability, liquidity, and leverage have significant influence on tax aggressiveness.